Multifunctional cement-based supercapacitor immersed tube tunnel intelligent lining and construction method thereof
Patent Information
- Application Number
- CN202611244687.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-17
- Publication Date
- 2026-10-16
AI Technical Summary
[0005]针对现有技术的不足,本发明提供了多功能水泥基超级电容器沉管隧道智能衬砌及其施工方法,改善了深海海底沉管隧道环境恶劣,传统的隧道衬砌结构功能单一,难以满足日益增长的运营储能需求;现有的储能系统占用隧道内部净空大且在潮湿盐雾环境中容易腐蚀受潮,导致系统短路失效或使用寿命下降,缺乏将电化学储能结构与承重衬砌结构融合,并在高压水环境中实现密封防腐的问题
1、本发明将底封层与外封层采用聚脲弹性体融合形成密闭腔体,并通过抽真空保压消除层间气隙,构筑无气隙的负压实体包覆结构,排除了内部氧气以防止电极腐蚀,且能有效抵抗深海高压挤压破坏;同时,正负极活性层采用掺入水系凝胶电解质的改性水泥基复合浆料制成,利用双液通道同步引发原位聚合构建离子传输网络,将储能器件直接融入隧道衬砌,在防止电解液渗漏的同时,大幅节省了传统独立储能设备对隧道净空的占用。
Smart Images

Figure CN122919033A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the fields of immersed tunnel engineering and electrochemical energy storage technology, specifically to intelligent lining of multifunctional cement-based supercapacitor immersed tunnels and its construction method. Background Technology
[0002] Immersed tunnels are commonly used in undersea transportation projects. The lighting, ventilation, and monitoring equipment inside the tunnels require a continuous power supply, thus increasing the demand for energy storage facilities. Currently, tunnel energy storage mostly uses external conventional battery cabinet systems. These external battery cabinets occupy significant space inside the tunnel, making their placement difficult in immersed tunnels with limited cross-sectional dimensions. The operating environment of undersea tunnels is characterized by high humidity and high salt spray; independent battery equipment exposed to this environment is prone to corrosion of its metal terminals and wiring, resulting in decreased insulation performance, increased risk of short circuits, and shortened equipment lifespan.
[0003] In addition, the current immersed tunnels face many pain points during operation: In terms of structural health monitoring, traditional discrete sensors have short lifespans and are too scattered, which easily creates a large number of monitoring blind spots; in terms of structural corrosion prevention, the high chloride ion environment in the ocean can easily lead to steel corrosion, while the construction and maintenance costs of traditional impressed current cathodic protection systems are high; in terms of fire safety management, traditional point fire detectors often have slow response in the narrow and confined space of the tunnel.
[0004] To save space within tunnels, structural energy storage technologies that combine electrochemical energy storage devices with building materials are gaining increasing attention. Using the tunnel lining and other building structures themselves as energy storage carriers can reduce the space occupied by independent energy storage devices. However, in the high-pressure water environment of the deep sea, existing cement-based structural energy storage devices suffer from insufficient sealing and corrosion resistance. Ordinary cement-based composite materials contain microscopic capillary pores, which, under the long-term influence of external high-pressure seawater, allow moisture and chloride ions to easily penetrate the material. This not only dilutes or leaks the electrolyte within the energy storage structure but also causes severe structural corrosion. The stainless steel current collector inside the material undergoes intense electrochemical corrosion upon contact with infiltrated moisture, oxygen, and high concentrations of chloride ions, damaging the physical / electrical interface between the current collector and the active layer, leading to increased internal resistance and decreased capacitance performance in the energy storage unit. Currently, there is a lack of tunnel lining technology solutions that can adapt to harsh high-pressure environments, possess both load-bearing and large-scale energy storage capabilities, and maintain stable long-term sealing and corrosion resistance. Summary of the Invention
[0005] To address the shortcomings of existing technologies, this invention provides a multifunctional cement-based supercapacitor immersed tunnel intelligent lining and its construction method, which improves the harsh environment of deep-sea immersed tunnels. Traditional tunnel lining structures have limited functions and cannot meet the growing operational energy storage demands. Existing energy storage systems occupy a large amount of internal tunnel clearance and are prone to corrosion and moisture in humid salt spray environments, leading to system short-circuit failures or reduced service life. Furthermore, there is a lack of integration of electrochemical energy storage structures with load-bearing lining structures and the achievement of sealing and corrosion prevention in high-pressure water environments.
[0006] To achieve the above objectives, the present invention provides the following technical solution: In a first aspect, the present invention provides a multifunctional intelligent lining for cement-based supercapacitor immersed tunnels, employing the following technical solution: A multifunctional cement-based supercapacitor immersed tunnel intelligent lining includes a substrate load-bearing layer and a supercapacitor thin layer disposed on the inner surface of the substrate load-bearing layer. The substrate load-bearing layer contains embedded positive and negative electrode leads, energy storage terminals, fire early warning temperature sensing points, stress and strain acquisition nodes, and cathodic protection current output terminals. The supercapacitor thin layer is composed of several independent sealing modules. Each independent sealing module, inwardly, includes a bottom sealing layer, a negative electrode current collector, a negative electrode active layer, a diaphragm layer, a positive electrode active layer, a positive electrode current collector, and an outer sealing layer. The bottom sealing layer and... The outer sealing layer together constitutes the sealing layer; both the bottom sealing layer and the outer sealing layer are polyurea elastomers, which fuse at the boundary to form a sealed cavity. The interior of the sealed cavity is vacuumed to a negative pressure state without air gaps; the negative electrode and positive electrode active layers are both made of modified cement-based composite slurry containing silicate cement, conductive filler and aqueous gel electrolyte; the aqueous gel electrolyte is formed by in-situ polymerization of a precursor solution containing potassium hydroxide, deionized water, acrylamide monomer, potassium persulfate initiator, N,N′-methylenebisacrylamide crosslinking agent and tetramethylethylenediamine catalyst.
[0007] By adopting the above technical solution, the bottom sealing layer and the outer sealing layer are fused at the boundary to form a complete encapsulation structure. The physicochemical stability of the polyurea elastomer prevents external moisture from entering the capacitor. The sealed cavity is in a gapless negative pressure state, which removes residual moisture and oxygen, prevents oxidation and corrosion of the electrode current collector, and ensures that the bottom sealing layer and the outer sealing layer are tightly attached to the internal functional layer. The negative and positive electrode active layers form a porous solid skeleton through silicate cement hydration, providing structural support. Conductive fillers are distributed inside the cement skeleton to form an electronic conductive network, and aqueous gel electrolyte fills the pores to provide ion transport channels.
[0008] The energy storage and multi-functional operation mechanism of this technical solution is as follows: Gel electrolyte network construction process: The present invention adopts a process of in-situ composite of cement matrix and aqueous gel electrolyte to construct electrolyte network: First, cement powder and conductive filler are dry mixed evenly, and a pre-prepared aqueous gel precursor solution is added to make the main slurry. Then, at the moment of spray molding, catalyst solution and initiator aqueous solution are simultaneously added through dual liquid channels to trigger in-situ crosslinking polymerization reaction and spraying operation is performed.
[0009] After spraying, the acrylamide monomers, under the synergistic effect of initiators, crosslinking agents, and catalysts, self-grow within the porous solid framework formed by cement hydration products to form a three-dimensional continuous polyacrylamide aqueous gel network. This gel network fills the capillary pores and micro-defects within the cement matrix, effectively binding alkaline electrolyte ions and constructing interconnected ion transport channels. This network structure firmly confines water molecules, potassium ions, and hydroxide ions within the cement matrix, thereby preventing electrolyte leakage under high-pressure environments.
[0010] The charging and discharging process of double-layer energy storage: The core mechanism of the charging and discharging process is the physical adsorption-desorption of the interfacial double layer. In the charging state, the positive electrode active layer loses electrons through the external circuit, while the negative electrode active layer gains electrons. Hydroxide ions and potassium ions in the aqueous gel network migrate to the interface of the positive and negative electrode active layers, respectively, driven by an external electric field, and are physically adsorbed on the surface of the conductive filler and the porous interface, thus constructing a stable charge accumulation double layer at the solid-liquid interface to achieve charge storage. In the discharge state, ions adsorbed at the interface undergo reversible reverse desorption and flow back along the gel ion channels, while electrons are directionally transported through the external circuit to release electrical energy. The conversion of electrical energy into chemical energy is achieved through the physical adsorption and desorption of ions at the conductive interface. Simultaneously, the ion transport network formed by the porous framework of cement hydration and the in-situ polymerized three-dimensional gel ensures rapid ion migration. Combined with the electronic insulation of the diaphragm and the liquid retention and humidity control mechanism of the sealed cavity, the system achieves stable charge-discharge energy storage characteristics over long cycles.
[0011] Structural health monitoring mechanism (pressure-sensitive characteristics): When the tunnel lining is subjected to stress deformation or microcracks are generated, the geometry of the porous conductive network in the supercapacitor thin layer changes accordingly, causing regular changes in the electron transition barrier and equivalent resistance (causing regular fluctuations in internal resistivity and equivalent resistance), thereby realizing distributed structural stress and strain monitoring and crack location without blind spots in the whole area. This is further combined with the stress and strain acquisition nodes pre-embedded in the load-bearing layer of the matrix for data calibration and precise quantitative verification. Fire early warning mechanism (temperature-sensitive characteristics): When a fire occurs in the tunnel and the local temperature rises abnormally, the thermal motion of ions in the aqueous gel electrolyte intensifies, and the electrical parameters such as internal impedance undergo drastic changes. The system monitors this change to achieve a rapid distributed fire alarm response. In addition, it combines the pre-embedded fire early warning temperature sensing points to perform temperature truth calibration and accurate verification of fire alarm. Cathodic protection system mechanism: The supercapacitor thin layer itself can act as an auxiliary anode, using its stored electrical energy to output cathodic protection current to the steel mesh in the load-bearing layer of the substrate, so that the internal steel is at polarization potential, thus constructing a long-term and low-cost active anti-corrosion system. System Control Mechanism: This system is connected to a shore-based control center, which integrates intelligent energy management and monitoring / early warning algorithms. It collects real-time data on the resistance and capacitance parameters of the supercapacitor's thin layer, as well as temperature, stress, and strain parameters of the pre-embedded sensing nodes. This data is then used to fuse and calculate crack location and fire alarm signals, and to allocate energy storage and external anti-corrosion current, achieving comprehensive system scheduling and management.
[0012] Preferably, the modified cement-based composite slurry is made from the following raw materials in parts by weight: 100 parts of 42.5 grade ordinary Portland cement, 10 to 15 parts of conductive filler, and 60 to 160 parts of aqueous gel electrolyte precursor solution and initiation system; the aqueous gel electrolyte precursor solution and initiation system are made from the following raw materials in parts by weight: 5 to 9 parts of potassium hydroxide, 88 to 92 parts of deionized water, 3 to 7 parts of acrylamide, 0.035 to 0.084 parts of potassium persulfate, 0.015 to 0.042 parts of N,N′-methylenebisacrylamide crosslinking agent, and 0.0045 to 0.0105 parts of tetramethylethylenediamine catalyst.
[0013] By adopting the above technical solution, the amount of conductive filler exceeds the permeation critical value of the composite system, ensuring the establishment of a continuous electron transport channel within the cement insulating matrix. The mass ratio of the aqueous gel electrolyte precursor to the components in the initiation system maintains the viscoelasticity and ionic conductivity balance of the gel system, preventing false setting or abnormal rapid setting of the cement slurry caused by a strongly alkaline environment.
[0014] Preferably, the innermost surface of the supercapacitor thin layer is provided with a fireproof decorative layer; the viscosity of the final composite slurry of the aqueous gel electrolyte is 6000 to 7000 mPa·s; the supercapacitor thin layer is a thin layer structure without coarse aggregate, with an overall thickness of 11.3 to 23.1 mm.
[0015] By adopting the above technical solution, the fireproof decorative layer isolates the heat generated during tunnel operation. Regarding the rheological properties of the system, the precursor solution of the aqueous gel electrolyte exhibits an initial viscosity of 1.0 to 2.4 mPa·s before in-situ polymerization (this viscosity changes linearly with the acrylamide dosage, e.g., approximately 1.7 mPa·s at a 5% dosage). This low viscosity greatly promotes its uniform wetting and mixing with cement and conductive fillers. The resulting modified cement-based composite slurry has an overall apparent viscosity of 6000 to 7000 mPa·s, giving it excellent thixotropic properties, thus meeting the anti-sagging construction requirements for facade and roof spraying operations. Furthermore, the coarse aggregate-free thin-layer structure avoids the cutoff effect of coarse aggregate on the conductive network, reducing contact resistance and saving internal tunnel clearance.
[0016] Preferably, the conductive filler is conductive carbon black or a composite filler of conductive carbon black and chopped carbon fibers; the thickness of the negative electrode and positive electrode active layers is 3 to 7 mm.
[0017] By employing the above technical solution, conductive carbon black particles provide an ion adsorption interface with a high specific surface area, while short-cut carbon fibers form long-range conductive bridges within the slurry. The combination of these two components generates a synergistic conductive effect, reducing the internal resistance to charge transfer. The limited thickness of the active layer ensures that electrolyte ions can penetrate into the electrode, improving the specific capacitance utilization rate of the active material.
[0018] Since electrolyte ions need to migrate within a cement-based gel network, an excessively thick active layer significantly increases the migration path and resistance of the ions. Controlling the thickness to 3 to 7 mm can effectively shorten the ion migration distance, reduce concentration polarization, and ensure that the active material deep inside the electrode can also efficiently participate in the rapid electrochemical charge-discharge reaction, thereby effectively improving the specific capacitance utilization of the active material.
[0019] Preferably, the load-bearing matrix comprises an outer seawater erosion-resistant protective layer and an inner reinforced concrete load-bearing layer. The protective layer is C120 grade ultra-high performance concrete with 2-3 parts by weight of nano-silica added, and the chloride ion diffusion resistance coefficient of the C120 grade ultra-high performance concrete is <0.5×10⁻⁶. -12 m 2 / s.
[0020] By adopting the above technical solution, nano-silica can not only fill the nanoscale pores inside ultra-high performance concrete, thus densifying the matrix structure, but also undergo a secondary pozzolanic reaction with calcium hydroxide produced during the early hydration of cement to generate hydrated calcium silicate with cementitious properties. The generated hydrated calcium silicate fills the capillary pores inside the ultra-high performance concrete, cutting off the penetration path of seawater and chloride ions, and protecting the internal capacitive layer and load-bearing steel bars from corrosion.
[0021] Preferably, the polyurea elastomer is an aliphatic polyurea with a tensile strength ≥20MPa, an elongation at break ≥300%, and an adhesion strength ≥2MPa to the supercapacitor thin layer; the bottom sealing layer has a thickness of (2.0±0.2)mm; and the negative pressure vacuum degree inside the sealed cavity is -0.09MPa or below.
[0022] By adopting the above technical solution, the aliphatic polyurea molecular structure does not contain benzene rings, reducing the probability of UV aging and oxidation. Tensile strength and elongation at break enable the sealing layer to adapt to deformation, absorbing the micro-deformation of tunnel sections under foundation settlement and maintaining structural airtightness. The established negative pressure ensures that the bottom and outer sealing layers adhere tightly to the internal functional layers, forming a dense, gapless structure that blocks the intrusion of external moisture and oxygen.
[0023] Preferably, both the negative and positive current collectors are made of 0.1 mm thick stainless steel wire mesh; the diaphragm layer is made of glass fiber reinforced cement slurry containing ordinary silicate cement, deionized water, glass fiber, silica fume, polycarboxylate superplasticizer, and potassium hydroxide, with a thickness of 1.5 to 2.5 mm; the independent sealing module has an area of 8 to 15 m². 2 The boundary is covered with polytetrafluoroethylene insulating strips; the positive and negative electrode leads extend from the load-bearing layer of the substrate through the bottom sealing layer, with a diameter of 8 to 12 mm, and the sealing protection at the welding point with the current collector reaches IP68 level.
[0024] By adopting the above technical solutions, the stainless steel wire mesh exhibits alkali corrosion resistance, and its mesh pores facilitate the penetration and bonding of slurry and electrolytes. Glass fiber reinforced cement slurry provides both electronic insulation between the positive and negative electrodes, while the pore channels also allow for ion conductivity. Modular zoning limits the systemic failure of the entire energy storage network caused by localized mechanical damage, and PTFE insulation strips cut off leakage paths between different modules, improving system operational safety. Simultaneously, the pre-embedded energy storage terminals, temperature sensing points, stress and strain acquisition nodes, and cathodic protection output terminals provide a robust hardware interface and data acquisition channel for the system to achieve its integrated functions of energy storage, fire early warning, structural monitoring, and corrosion protection.
[0025] Secondly, this invention provides a construction method for intelligent lining of a multifunctional cement-based supercapacitor immersed tunnel, employing the following technical solution: A construction method for intelligent lining of a multifunctional cement-based supercapacitor immersed tunnel includes: integrally casting a load-bearing base layer and pre-embedding positive and negative electrode leads, energy storage terminals, fire early warning temperature sensing points, stress and strain acquisition nodes, and cathodic protection current output terminals; grinding the inner surface of the load-bearing base layer and applying an epoxy resin interface agent; dividing the inner surface into several modular areas and laying insulating strips at the boundaries; and using an automated spraying robot to sequentially spray the bottom sealing layer, lay the negative electrode current collector, and weld it to the negative electrode leads extending from the load-bearing base layer. The negative electrode active layer, glass fiber reinforced cement-based diaphragm layer, and positive electrode active layer are sprayed sequentially. During the spraying of the positive and negative electrode active layers, a pre-mixed slurry containing cement, conductive filler, and aqueous gel electrolyte precursor is pumped to the spray gun and simultaneously added to the initiation system through a dual-liquid channel to trigger in-situ cross-linking polymerization. The positive electrode current collector is laid and welded to the positive electrode lead wire. Finally, an outer sealing layer is sprayed to form a sealed cavity. The bottom sealing layer and the outer sealing layer together constitute a sealing layer. The formed structure is moved into a sealed kiln for standard curing. After curing, the sealed cavity is evacuated and pressurized to ensure that the bottom sealing layer and the outer sealing layer are tightly attached to the internal functional layer. Finally, the port is sealed and a fireproof decorative layer is applied to the inside.
[0026] By adopting the above technical solution, all processes are completed in the factory prefabrication stage, avoiding damage to energy storage devices caused by the high humidity and salt spray environment during in-situ subsea construction. Grinding and applying epoxy resin interface agent seals the original pores in the substrate, improving the adhesion of the undersealing layer. Automated spraying operations control the thickness consistency of the multi-layer composite thin layers, reducing contact resistance caused by physical gaps between coating interfaces. Vacuuming and pressure holding processes eliminate air bubbles and moisture between layers, ensuring a tight seal between the undersealing layer and the outer sealing layer around the internal functional layer, maintaining the service life of the internal active energy storage material.
[0027] Preferably, the method for preparing the modified cement-based composite slurry includes: dissolving potassium persulfate to form an initiator aqueous solution, diluting tetramethylethylenediamine to form a catalyst solution, and sealing both separately for later use; Potassium hydroxide was added to deionized water and stirred until dissolved. After cooling to room temperature, acrylamide monomer and N,N′-methylenebisacrylamide crosslinking agent were uniformly added under mechanical stirring to prepare an aqueous gel electrolyte precursor solution. Cement powder and conductive filler are dry-mixed evenly, and the above-mentioned precursor solution is added and stirred evenly to form a main slurry without an initiation system, which is then pumped and transported. At the spray gun end of the spraying robot, the prepared catalyst solution and initiator aqueous solution are simultaneously combined with the main slurry through independent liquid delivery channels, triggering an in-situ polymerization reaction at the moment of spraying, thus completing the spraying and forming of the modified cement-based composite slurry.
[0028] By adopting the above technical solution, potassium hydroxide is first dissolved in deionized water and stirred until dissolved. After cooling to room temperature by natural heat dissipation, acrylamide monomer and polymerization aids are added. Then, the main slurry is prepared and the initiator and catalyst are added simultaneously through a dual-liquid channel at the spray gun end. This process not only avoids the high temperature problem caused by strong exothermic dissolution of strong alkali, but also avoids premature cross-linking and curing of monomers and aids during the stirring and conveying stage, which could lead to equipment blockage. This ensures that the slurry has good construction and spraying performance.
[0029] Preferably, the surface roughness Ra is controlled to be ≥30μm during grinding; the spraying pressure is controlled to be 15 to 18MPa, the spray gun speed is controlled to be 0.8 to 1.2m / s, and the coating thickness error is within ±0.5mm; the standard curing is 20℃, relative humidity ≥95%, for 28 days; the test port is sealed after vacuuming to -0.09MPa and holding the pressure for 30min.
[0030] By adopting the above technical solutions, the roughness range increases the anchoring points on the substrate surface. The high-pressure spraying process allows the slurry to adhere to the substrate surface and expel any air trapped inside, forming a dense functional layer structure. The standard curing regime with constant temperature and humidity satisfies the hydration conditions of tricalcium silicate and dicalcium silicate in the modified cement-based composite slurry, constructing a framework of hydration products.
[0031] This invention provides a multifunctional intelligent lining for immersed tunnels using cement-based supercapacitors and its construction method. It offers the following advantages: 1. This invention uses polyurea elastomer to fuse the bottom sealing layer and the outer sealing layer to form a sealed cavity, and eliminates the interlayer air gap by vacuuming and pressurizing, constructing a gapless negative pressure solid encapsulation structure, which eliminates internal oxygen to prevent electrode corrosion and can effectively resist the damage caused by the high pressure of deep sea. At the same time, the positive and negative electrode active layers are made of modified cement-based composite slurry with water-based gel electrolyte, and the in-situ polymerization is initiated by dual liquid channels to construct an ion transport network, directly integrating the energy storage device into the tunnel lining. While preventing electrolyte leakage, it greatly saves the tunnel clearance occupied by traditional independent energy storage equipment.
[0032] 2. This invention divides the supercapacitor thin layer into several independent sealed modules separated by insulating strips, cutting off the leakage path and effectively limiting systemic cascading failures caused by local mechanical damage. All coating processes are completed in the factory prefabrication stage using automated high-pressure spraying and vacuum equipment, which not only avoids the interference of the in-situ high-humidity salt spray environment on the seabed, but also ensures the consistency of the thickness of each composite thin layer, effectively reducing the contact resistance caused by the physical gap at the interface, and ensuring the long-term stability of the device's electrochemical performance.
[0033] 3. This invention relies on the intrinsic piezoresistive and thermosensitive characteristics of the thin-layer supercapacitor to achieve full-range, blind-spot-free detection of structural deformation and abnormal temperature rise by monitoring internal impedance fluctuations. It also works with firmly embedded sensing nodes inside the substrate for data calibration and alarm verification. Simultaneously, it utilizes the electrical energy stored in the device itself as an auxiliary anode to directly output cathodic protection polarization current to the internal steel reinforcement, achieving a high degree of integration of electrical energy storage, health monitoring, fire early warning, and active corrosion prevention, effectively reducing the cost of independent construction and comprehensive maintenance of multiple tunnel systems. Attached Figure Description
[0034] Figure 1 This is a cross-sectional view of the overall structure of the intelligent lining for immersed tunnels according to the present invention; Figure 2 This is a schematic diagram of the thin layer of the cement-based supercapacitor of the present invention; Figure 3 This is an enlarged view of the thin-layer structure of the cement-based supercapacitor of the present invention; Figure 4 This is a flowchart of the intelligent lining construction process for immersed tunnels according to the present invention; Figure 5 This is a block diagram of the shore-based control center energy and monitoring management system of the present invention.
[0035] Among them, 1. UHPC; 2. Reinforced concrete load-bearing layer; 3. Cement-based supercapacitor thin layer; 4. Fireproof decorative layer; 5. Base plate; 6. Auxiliary compartment; 7. Partition wall; 8. Lane compartment; 9. Auxiliary compartment partition wall; 30. Supercapacitor; 31. Sealing layer; 301. 316L stainless steel wire mesh negative electrode current collector; 302. Negative electrode active layer (cement-based functional slurry); 303. Glass fiber reinforced cement slurry membrane layer; 304. Positive electrode active layer (cement-based functional slurry); 305. 316L stainless steel wire mesh positive electrode current collector. Detailed Implementation
[0036] The technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0037] Preparation Examples 1-5: Preparation Example 1: This preparation example provides an aqueous gel electrolyte precursor solution and its initiation system, including the following steps: The following components are listed in parts by mass, which refers to the relative proportions between the components and does not limit the total parts by mass of the components to 100 parts.
[0038] Accurately weigh 92 parts by weight of deionized water, 5 parts by weight of potassium hydroxide, 3 parts by weight of acrylamide, 0.035 parts by weight of potassium persulfate, 0.015 parts by weight of N,N'-methylenebisacrylamide crosslinking agent, and 0.0045 parts by weight of tetramethylethylenediamine catalyst.
[0039] At room temperature, potassium hydroxide is first slowly added to deionized water and stirred until it is fully dissolved and the solution is cooled to room temperature to form a homogeneous alkaline solution. Then, under mechanical stirring, acrylamide powder and N,N'-methylenebisacrylamide crosslinking agent are uniformly added to the alkaline solution and stirred until completely dissolved to obtain an aqueous gel electrolyte precursor solution with extremely low viscosity (about 1.0±0.1 mPa·s). Meanwhile, potassium persulfate was dissolved in a small amount of deionized water to form an initiator aqueous solution, and tetramethylethylenediamine was diluted in a small amount of deionized water to form a catalyst solution. The two were placed in separate containers and sealed for later use to avoid premature contact and redox reaction failure. The deionized water used for dissolution or dilution is included in the above-mentioned deionized water mass fraction and will be added later when mixing with cement to trigger in-situ polymerization. The resulting aqueous gel electrolyte precursor solution should be used within 4 hours after preparation to avoid the acrylamide monomer from being left in a strongly alkaline environment for a long time, which would lead to a decrease in hydrolysis or polymerization activity.
[0040] Preparation Example 2: This preparation example provides an aqueous gel electrolyte precursor solution and its initiation system, including the following steps: Accurately weigh 90 parts by weight of deionized water, 7 parts by weight of potassium hydroxide, 5 parts by weight of acrylamide, 0.06 parts by weight of potassium persulfate, 0.03 parts by weight of N,N'-methylenebisacrylamide crosslinking agent, and 0.0075 parts by weight of tetramethylethylenediamine catalyst.
[0041] At room temperature, potassium hydroxide is first slowly added to deionized water and stirred until it is fully dissolved and cooled to room temperature to form a homogeneous alkaline solution. Then, under strong mechanical stirring, acrylamide powder and N,N'-methylenebisacrylamide crosslinking agent are added and dissolved to prepare an aqueous gel electrolyte precursor solution with an initial viscosity of about 1.7±0.2 mPa·s. Potassium persulfate was dissolved in a small amount of deionized water to form an initiator aqueous solution, and tetramethylethylenediamine was diluted in a small amount of deionized water to form a catalyst solution. Both were sealed separately for later use, and the deionized water used for dissolution or dilution was included in the above-mentioned deionized water mass fraction.
[0042] Preparation Example 3: This preparation example provides an aqueous gel electrolyte precursor solution and its initiation system, including the following steps: Accurately weigh 88 parts by weight of deionized water, 9 parts by weight of potassium hydroxide, 7 parts by weight of acrylamide, 0.084 parts by weight of potassium persulfate, 0.042 parts by weight of N,N'-methylenebisacrylamide crosslinking agent, and 0.0105 parts by weight of tetramethylethylenediamine catalyst.
[0043] At room temperature, potassium hydroxide is first slowly added to deionized water and stirred. After the exothermic dissolution process ends and the solution is cooled to room temperature, a high-concentration alkaline solution is formed. Then, under strong mechanical shear stirring, acrylamide powder and N,N'-methylenebisacrylamide are slowly added in batches and dissolved to prepare an aqueous gel electrolyte precursor solution with a viscosity of approximately 2.4 ± 0.2 mPa·s. Potassium persulfate and tetramethylethylenediamine are sealed separately for later use.
[0044] Preparation Example 4: This preparation example provides a basic ratio of electrode active layer composite slurry, including the following steps: Weigh out 100 parts by weight of 42.5 grade ordinary silicate cement, 15 parts by weight of conductive carbon black, and 60 parts by weight of the aqueous gel electrolyte precursor solution and initiation system prepared in Preparation Example 2, after adjusting for the proportions described in Preparation Example 2.
[0045] The above-mentioned cement powder without coarse aggregate and conductive carbon black were dry-mixed evenly in a dry mixer to ensure the dispersion of conductive filler. Then, an aqueous gel electrolyte precursor solution was added, and while stirring, the prepared catalyst solution and initiator aqueous solution were added to the mixing tank separately and simultaneously through a dual-liquid channel. The mixture was stirred in a stepwise manner from low speed to high speed. While relying on the alkaline solution to activate the early hydration of cement, the initiation system triggered the in-situ cross-linking polymerization of acrylamide monomers inside the cement paste, thus preparing a uniform, non-agglomerated modified cement-based composite slurry with a final viscosity controlled at approximately 6000 mPa·s. The viscosity was the apparent viscosity measured within 5 minutes after mixing at 25°C. This slurry was used as the raw material for subsequent spraying of the positive electrode active layer 304 (cement-based functional slurry) and the negative electrode active layer 302 (cement-based functional slurry).
[0046] Preparation Example 5: This preparation example provides an optimized formulation of an electrode active layer composite slurry, comprising the following steps: By weight, 100 parts of 42.5 grade ordinary silicate cement, 10 parts of composite conductive filler (the filler is composed of conductive carbon black and short-cut carbon fiber in a mass ratio of 7:3, and the short-cut carbon fiber has a length of 3-6 mm), and 65 parts of the total amount of the aqueous gel electrolyte precursor solution and initiation system prepared in Preparation Example 3, after being converted according to the proportions described in Preparation Example 3.
[0047] The above-mentioned cement powder and composite conductive filler are dry-mixed evenly to ensure that the short-cut carbon fibers are evenly dispersed and do not entangle or agglomerate. Subsequently, an aqueous gel electrolyte precursor solution was added, along with prepared tetramethylethylenediamine and potassium persulfate, and the mixture was vigorously stirred to induce an in-situ polymerization reaction, preparing a homogeneous modified cement-based composite slurry for subsequent spraying. This slurry utilizes a conductive network synergistically constructed from chopped carbon fibers and conductive carbon black, which helps reduce the internal resistance of the electrode active layer. Simultaneously, reducing the amount of conductive carbon black improves the slurry's dispersibility and sprayability.
[0048] Preparation Example 6: This preparation example provides a glass fiber reinforced cementitious membrane slurry, including the following steps: Weigh out 100 parts of 42.5 grade ordinary Portland cement, 35 to 45 parts of deionized water, 1.5 to 3 parts of glass fiber, 5 to 10 parts of silica fume, 0.2 to 0.5 parts of polycarboxylate superplasticizer, and 3 to 6 parts of potassium hydroxide by weight.
[0049] After dry mixing cement, silica fume, and glass fiber until uniform, an aqueous solution containing potassium hydroxide and polycarboxylate superplasticizer is added. The mixture is stirred at low speed for 2 to 3 minutes, followed by high speed for 3 to 5 minutes to obtain a homogeneous glass fiber reinforced cement-based diaphragm slurry. The cured diaphragm slurry possesses ion conductivity and electronic insulation, serving to isolate the negative electrode active layer 302 and the positive electrode active layer 304, preventing direct short circuit between the positive and negative electrodes.
[0050] Examples 1-3: Example 1: This embodiment provides a multifunctional cement-based supercapacitor immersed tunnel intelligent lining and its construction method, the overall structural cross-section of which is shown below. Figure 1 As shown, its construction process is as follows: Figure 4 As shown, it includes the following steps: (1) Precast substructure: A seawater erosion resistant protective layer of ultra-high performance concrete (UHPC) 1 with a thickness of 80-120mm is integrally cast in the precast plant, along with a reinforced concrete load-bearing layer 2 with a thickness of 900-1300mm. UHPC 1 is made of C120 grade ultra-high strength concrete, with a chloride ion diffusion resistance coefficient of <0.5×10 -12 m 2 / s. Combined Figure 1As shown, during the pouring process, the bottom slab 5, partition wall 7, and auxiliary compartment partition wall 9 of the immersed tunnel are simultaneously formed, thus constructing the complete main frame structure of the lane compartment 8 and auxiliary compartment 6. Two parts by mass of nano-silica are added to the interior of UHPC1. Holes are pre-reserved inside the reinforced concrete structure to simultaneously pre-embed positive and negative electrode leads with a diameter of 8mm, energy storage terminals, fire early warning temperature sensing points, stress and strain acquisition nodes, cathodic protection current output terminals, and humidity and pressure sensors. Curing is carried out to the design strength.
[0051] (2) Grinding treatment of the base layer: The inner surface of the lining is ground by an automated grinding robot to remove the surface laitance and oil stains, and the surface roughness Ra≥30μm is controlled. After cleaning the dust, a 0.3-0.5mm thick epoxy resin interface agent is evenly applied to seal the micropores of the base layer.
[0052] (3) Automated zoned spraying: The supercapacitor thin layer (3) is a thin layer structure without coarse aggregate, with an overall thickness of 12.5 to 23 mm. Combined with Figure 2 and Figure 3 The layered and overall structure of the cement-based supercapacitor thin layer 3 shown divides the inner surface of the lining into sections with an area of 8m². 2 Several independent sealed modules, with module boundaries using a volume resistivity ≥1×10⁻⁶. 18 Ω A PTFE insulating strip of cm is used for physical separation. The automated spraying robot is then started (spraying pressure set to 15MPa, spray gun moving speed 0.8m / s, layer thickness error ±0.5mm) to perform the forming operation sequentially: Bottom sealing layer: A layer of aliphatic polyurea elastomer with a thickness of (2.0±0.2) mm is uniformly sprayed as a sealing layer 31. The bottom layer not only serves as a one-time sealing bottom film to fill the base layer, but also acts as an insulating isolation film. Its tensile strength is ≥20MPa, elongation at break is ≥300%, and its bonding strength with the supercapacitor thin layer 3 is ≥2MPa. Negative current collector: Lay a 0.1mm thick 316L stainless steel wire mesh negative current collector 301 with an overlap width of 50mm. Its end is argon arc welded to the pre-embedded negative electrode lead wire that passes through the bottom sealing layer from the load-bearing layer of the substrate. The weld point is insulated and sealed with epoxy resin. Capacitor functional layer: The 3mm negative electrode active layer 302 (cement-based functional slurry) provided in Preparation Example 4, the 1.5mm glass fiber reinforced cement slurry membrane layer 303 provided in Preparation Example 6, and the 3mm positive electrode active layer 304 (cement-based functional slurry) are sprayed sequentially to ensure a tight wet-to-wet bond between the layers. Positive current collector: A 0.1mm thick 316L stainless steel wire mesh positive current collector 305 is laid, and its end is argon arc welded to the pre-embedded positive electrode lead wire, and the welding and sealing are completed. Outer sealing layer: A 3mm thick outer layer of aliphatic polyurea elastomer is sprayed as a sealing layer 31, seamlessly integrating with the underlying polyurea at the boundary. During the previous integral casting stage of the load-bearing substrate, energy storage terminals, fire early warning temperature sensing points, stress and strain acquisition nodes, cathodic protection current output terminals, and humidity and pressure sensors, among other multi-functional nodes, were pre-embedded securely within it. Therefore, when spraying the outer sealing layer, only the exposed electrode active layer / diaphragm layer and the positive and negative electrode lead wire nodes that have already penetrated the bottom sealing layer and been welded to the current collector need to be covered. Waterproof sealing treatment (reaching IP68 protection) is also applied to the lead wire penetration points, ultimately forming an independent, sealed, multi-functional cavity.
[0053] (4) Constant temperature and humidity curing and vacuum sealing: The pipe section was moved into a sealed kiln with an ambient temperature of 20℃ and a relative humidity of ≥95% for 28 days of standard curing. The independent sealing module was evacuated to -0.09MPa and held for 30 minutes. After passing the airtightness test, the lead holes and detection ports were directly sealed with sealant while maintaining the negative pressure, so that the outer polyurea layer adhered tightly to the inner capacitor layer under the negative pressure. After the sealing and curing process was completed, a 25mm thick fireproof decorative layer 4 was applied to the innermost surface of the intelligent lining to complete the overall preparation. Figure 5 The diagram shown is a block diagram of the energy and monitoring management system of the shore-based control center. After the pipe section is put into operation, it can interact with the system through the submarine network to realize the overall scheduling and real-time safety early warning of energy storage array modules, wind power monitoring modules and health and fire monitoring modules.
[0054] Example 2: This embodiment provides a smart lining for a multifunctional cement-based supercapacitor immersed tunnel and its construction method, including the following steps: (1) Prefabrication of the substrate in the factory: The 80-120mm UHPC1 seawater erosion resistant protective layer and the 900-1300mm reinforced concrete load-bearing layer 2 are integrally cast. During casting, the base slab 5, auxiliary compartments 6, partition walls 7, driveway compartment 8 and auxiliary compartment partition walls 9 are integrally formed. 2.5 parts by weight of nano-silica are added to the interior of the protective layer. At the same time, 10mm diameter positive and negative electrode leads, energy storage terminals, fire early warning temperature sensing points 312, stress and strain acquisition nodes and cathodic protection current output terminals are pre-embedded in the load-bearing layer and cured.
[0055] (2) Grinding treatment of the base layer: The surface roughness Ra of the inner surface of the lining is controlled to be 75μm by automated grinding, and then a 0.3-0.5mm thick epoxy resin interface agent is evenly applied.
[0056] (3) Automated zoned spraying: The area of each module is 12m² 2Polytetrafluoroethylene (PTFE) insulating strips are laid between modules. A spraying robot (set spraying pressure 17.5 MPa, spray gun moving speed 1.0 m / s, layer thickness error ±0.5 mm) is used to form the layers sequentially, and the final thickness of each functional layer is controlled by adjusting the output per unit time and the number of spray passes. Bottom sealing layer: A bottom polyurea elastomer with a thickness of (2.0±0.2) mm is sprayed as a sealing layer 31, serving as a one-time sealing bottom film. The tensile strength of the polyurea elastomer is ≥20MPa, the elongation at break is ≥300%, and the bonding strength is ≥2MPa. Negative electrode current collector: A 0.1mm thick 316L stainless steel wire mesh is laid flat as the negative electrode current collector 301 (overlap width 50mm), and is argon arc welded to the pre-embedded negative electrode lead wire that passes through the base load-bearing layer and the bottom sealing layer and is sealed with IP68 grade epoxy anti-corrosion seal. Capacitor functional layer: Sequentially spray a 5mm negative electrode active layer 302 (cement-based functional slurry) provided in Preparation Example 4, a 2mm diaphragm layer 303 slurry provided in Preparation Example 6, and a 5mm positive electrode active layer 304 (cement-based functional slurry). Positive current collector: Lay and weld 316L stainless steel wire mesh positive current collector 305, the end of which is connected to the pre-embedded positive electrode lead wire by argon arc welding and is insulated and sealed. Outer sealing layer: A 3mm thick high-pressure airless polyurea elastomer is sprayed as a sealing layer 31 to fully cover the entire surface.
[0057] During the initial integral pouring stage of the substrate load-bearing layer, energy storage terminals, fire early warning temperature sensing points, stress and strain acquisition nodes, and cathodic protection current output terminals (i.e., a four-in-one node) were pre-embedded securely inside. Therefore, when spraying the outer sealing layer, only the exposed electrode active layer / diaphragm layer and the positive and negative electrode lead wire nodes that had previously penetrated the bottom sealing layer and been welded to the current collector need to be covered, and the lead wire penetration points need to be waterproofed and sealed (reaching IP68 protection level), ultimately forming an independent, sealed, multi-functional cavity.
[0058] (4) Constant temperature and humidity curing and vacuum sealing: The pipe section was moved into an environment with a temperature of 20℃ and a relative humidity of ≥95% for 28 days of standard curing. The independent module was evacuated to -0.09MPa and held for 30 minutes. After passing the airtightness test, the port was directly cured and sealed with sealant while maintaining the negative pressure. This allowed the outer polyurea layer to adhere tightly to the inner capacitor layer under the negative pressure. Finally, the fireproof decorative layer 4 was applied to the inner surface.
[0059] Example 3: This embodiment provides a smart lining for a multifunctional cement-based supercapacitor immersed tunnel and its construction method, including the following steps: (1) Prefabrication of the substrate in the factory: The 80-120mm UHPC1 seawater erosion resistant protective layer and the 900-1300mm reinforced concrete load-bearing layer 2 are poured integrally, and the main tunnel frame including the bottom slab 5, auxiliary compartments 6, partition walls 7, lane compartments 8 and auxiliary compartment partition walls 9 are prefabricated simultaneously. 3 parts by weight of nano-silica are added to the interior of the protective layer. Simultaneously, 12mm diameter 316L stainless steel positive and negative electrode leads 310, energy storage terminals, fire early warning temperature sensing points 312, stress and strain acquisition nodes and cathodic protection current output terminals are pre-embedded in the load-bearing layer, and then cured and formed.
[0060] (2) Grinding treatment of the base layer: The surface roughness Ra of the inner surface of the lining is controlled to be 100μm by automated grinding. After cleaning, a 0.3-0.5mm thick epoxy resin interface agent is applied.
[0061] (3) Automated zoned spraying: The area of each module is 15m² 2 Polytetrafluoroethylene (PTFE) insulating strips are installed between modules. A spraying robot (set spraying pressure 18MPa, spray gun moving speed 1.2m / s, layer thickness error ±0.5mm) is used for rapid sequential forming, and the final thickness of each functional layer is controlled by adjusting the output per unit time and using multiple overlapping spraying methods. Bottom sealing layer: A 3mm thick layer of polyurea elastomer is sprayed as a sealing layer 31; Negative current collector: Lay 316L stainless steel wire mesh (overlap width 50mm), and its ends are argon arc welded and epoxy insulation adhesive applied to the pre-embedded negative electrode lead wire that passes through the base load-bearing layer and the bottom sealing layer. Capacitor functional layer: The optimized ratio negative electrode slurry (7 mm) provided in Preparation Example 5, the separator slurry (2.5 mm) provided in Preparation Example 6, and the positive electrode slurry (7 mm) were sequentially prepared by high-pressure spraying. Positive current collector: Lay a 316L stainless steel wire mesh for the positive electrode, and connect its ends to the pre-embedded positive electrode lead wire by argon arc welding and seal the connection. Outer sealing layer: A 3mm thick polyurea elastomer is sprayed over the entire structure as a sealing layer 31 to ensure edge closure. During the previous integral casting stage of the substrate load-bearing layer, energy storage terminals, fire early warning temperature sensing points, stress and strain acquisition nodes, and cathodic protection current output terminals (i.e., a four-in-one node) were pre-embedded securely within it. Therefore, when spraying the outer sealing layer, only the exposed electrode active layer / diaphragm layer and the positive and negative electrode lead wire nodes that have already penetrated the bottom sealing layer and been welded to the current collector need to be covered. Waterproof sealing treatment (reaching IP68 protection) is also applied to the lead wire penetration points, ultimately forming an independent, sealed, multi-functional cavity.
[0062] (4) Constant temperature and humidity curing and vacuum sealing: Standard curing for 28 days at 20℃ and humidity ≥95%. Vacuum to -0.09MPa and hold for 30 minutes. After confirming airtightness, perform permanent sealing on all exposed pipeline interfaces while maintaining negative pressure. This allows the outer polyurea layer to adhere tightly to the inner capacitor layer under negative pressure. Finally, cover the innermost surface of the structure with fireproof decorative layer 4 to complete the docking preparation.
[0063] Comparative Examples 1-5: Comparative Example 1: Compared with Example 1, the difference is that the two-liquid synchronous in-situ polymerization process was not used. Instead, the pre-synthesized polyacrylamide hydrogel was mechanically crushed and directly mixed with cement and conductive carbon black to form a slurry for spraying. The amount of acrylamide monomer, the amount of crosslinking agent, the potassium hydroxide content and the total water content in the polyacrylamide hydrogel were the same as in Example 1, and all other parameters were the same.
[0064] Comparative Example 2: Compared with Example 1, the difference is that: in step (4), no vacuuming was performed, and the port was directly sealed with sealant under normal pressure. The rest are the same.
[0065] Comparative Example 3: Compared with Example 2, the difference is that in step (1), no lead wires or nodes were pre-embedded inside the load-bearing layer; in step (3), the positive and negative lead wires and sensor cables directly penetrate the outer sealing layer to the inside (i.e., towards the internal space of the tunnel), and then sealant is applied locally to the surface of the exposed point. The rest is the same. This comparative example is used to examine the impact of the cable directly penetrating the outer sealing layer facing the high humidity and salt spray environment of the tunnel when the lead wire structure is not pre-embedded inside the load-bearing layer on the overall anti-corrosion and airtightness and long-term waterproof performance.
[0066] Comparative Example 4: Compared with Example 3, the difference is that the automated grinding process is omitted in step (2), but the process of applying epoxy resin interface agent is retained. That is, after applying 0.3-0.5mm thick epoxy resin interface agent to the un-grinded substrate surface that still has the original laitance, the base seal layer is sprayed. The rest are the same.
[0067] Comparative Example 5: Compared with Example 3, the difference is that the automated grinding process is retained in step (2), and the surface roughness of the lining is controlled to Ra of 100μm. However, the process of applying epoxy resin interface agent is omitted. After cleaning the dust, the bottom seal layer is directly sprayed. The rest are the same.
Claims
1. A multifunctional cement-based supercapacitor immersed tunnel intelligent lining, characterized in that, It includes a substrate load-bearing layer and a supercapacitor thin layer (3) disposed on the inner surface of the substrate load-bearing layer. The substrate load-bearing layer is pre-embedded with positive and negative electrode leads, energy storage terminals, fire early warning temperature sensing points, stress and strain acquisition nodes and cathodic protection current output terminals. The supercapacitor thin layer (3) is composed of several independent sealing modules. Each independent sealing module includes, in turn, a bottom sealing layer, a negative electrode current collector (301), a negative electrode active layer (302), a separator layer (303), a positive electrode active layer (304), a positive electrode current collector (305), and an outer sealing layer. The bottom sealing layer and the outer sealing layer together constitute a sealing layer (31). Both the bottom sealing layer and the outer sealing layer are polyurea elastomers, which fuse at the boundary to form a sealed cavity. The interior of the sealed cavity is vacuumed to create a negative pressure state with no air gaps. Both the negative electrode and the positive electrode active layer are made of a modified cement-based composite slurry containing silicate cement, conductive filler and aqueous gel electrolyte; The aqueous gel electrolyte is formed by in-situ polymerization of a precursor solution containing potassium hydroxide, deionized water, acrylamide monomer, potassium persulfate initiator, N,N′-methylenebisacrylamide crosslinking agent and tetramethylethylenediamine catalyst.
2. The intelligent lining according to claim 1, characterized in that, The modified cement-based composite slurry is made from the following raw materials in parts by weight: 100 parts of 42.5 grade ordinary Portland cement, 10 to 15 parts of conductive filler, and 60 to 160 parts of aqueous gel electrolyte precursor solution and initiation system; The aqueous gel electrolyte precursor solution and initiation system are made from the following raw materials in parts by weight: Potassium hydroxide 5 to 9 parts, deionized water 88 to 92 parts, acrylamide 3 to 7 parts, potassium persulfate 0.035 to 0.084 parts, N,N′-methylenebisacrylamide crosslinking agent 0.015 to 0.042 parts, tetramethylethylenediamine catalyst 0.0045 to 0.0105 parts.
3. The intelligent lining according to claim 1, characterized in that, The innermost surface of the supercapacitor thin layer (3) is provided with a fireproof decorative layer (4); The apparent viscosity of the final composite slurry of the aqueous gel electrolyte at 25°C is 6000 m to 7000 Pa·s. The supercapacitor thin layer (3) is a thin layer structure without coarse aggregate, with an overall thickness of 11.3 to 23.1 mm.
4. The intelligent lining according to claim 1, characterized in that, The conductive filler is conductive carbon black or a composite filler of conductive carbon black and short-cut carbon fibers. The thickness of both the negative and positive electrode active layers is 3 to 7 mm.
5. The intelligent lining according to claim 1, characterized in that, The load-bearing matrix includes an outer seawater erosion resistant protective layer (1) and an inner reinforced concrete load-bearing layer (2). The protective layer (1) is C120 grade ultra-high performance concrete with 2 to 3 parts by weight of nano-silica added. The chloride ion diffusion resistance coefficient of the C120 grade ultra-high performance concrete is <0.5×10⁻⁶. -12 m 2 / s.
6. The intelligent lining according to claim 1, characterized in that, The polyurea elastomer is an aliphatic polyurea, and the aliphatic polyurea has a tensile strength ≥20MPa, an elongation at break ≥300%, and a bonding strength with the supercapacitor thin layer (3) ≥2MPa. The thickness of both the bottom sealing layer and the outer sealing layer is (2.0±0.2) mm to (3.0±0.2) mm; The negative pressure vacuum inside the sealed cavity is -0.09 MPa or below.
7. The intelligent lining according to claim 1, characterized in that, Both the negative and positive current collectors are made of stainless steel wire mesh with a thickness of 0.1 mm; The membrane layer (303) is made of glass fiber reinforced cement slurry containing ordinary silicate cement, deionized water, glass fiber, silica fume, polycarboxylate superplasticizer and potassium hydroxide, and has a thickness of 1.5 to 2.5 mm. The area of the independent sealing module is 8 to 15 m². 2 The boundary is covered with polytetrafluoroethylene insulating strips; The positive and negative electrode leads extend outward from the load-bearing layer of the substrate and outward from the bottom sealing layer, with a diameter of 8 to 12 mm. The sealing protection at the welding point with the current collector reaches IP68 level.
8. A construction method for intelligent lining of multifunctional cement-based supercapacitor immersed tunnel, applied to the intelligent lining of multifunctional cement-based supercapacitor immersed tunnel as described in any one of claims 1-7, characterized in that, Includes the following steps: The integrally cast base load-bearing layer is pre-embedded with positive and negative electrode lead wires, energy storage terminals, fire early warning temperature sensing points, stress and strain acquisition nodes and cathodic protection current output terminals. The inner surface of the base load-bearing layer is polished and coated with epoxy resin interface agent. The inner surface is planned as a construction area of several independent modules and insulating strips are laid at the boundaries; An automated spraying robot is used to sequentially spray the base seal layer, lay the negative electrode current collector (301), and weld it to the negative electrode lead wires led out from the substrate load-bearing layer; The negative electrode active layer (302), glass fiber reinforced cement-based membrane layer (303), and positive electrode active layer (304) are sprayed sequentially. When the positive and negative electrode active layers are sprayed, the pre-mixed main slurry containing cement, conductive filler and aqueous gel electrolyte precursor is pumped to the spray gun. At the same time, the initiator aqueous solution and catalyst solution in the initiation system are respectively transported to the spray gun end through independent liquid delivery channels. The three are synchronously combined at the moment of spraying, so that the modified cement-based composite slurry is sprayed onto the wall surface to trigger in-situ cross-linking polymerization. A positive current collector (305) is laid and welded to the positive lead wire. Finally, an outer sealing layer is sprayed to form a sealed cavity. The bottom sealing layer and the outer sealing layer together constitute a sealing layer (31). The molded structure is moved into a closed kiln for standard curing. After curing, the closed cavity is evacuated and pressure is maintained so that the bottom sealing layer and the outer sealing layer are tightly attached to the internal functional layer. Finally, the port is sealed and a fireproof decorative layer is constructed on the inside (4).
9. The construction method according to claim 8, characterized in that, The method for preparing the modified cement-based composite slurry includes: Potassium persulfate was dissolved to form an initiator aqueous solution, and tetramethylethylenediamine was diluted to form a catalyst solution. Both were sealed separately for later use. Potassium hydroxide was added to deionized water and stirred until dissolved. After cooling to room temperature, acrylamide monomer and N,N′-methylenebisacrylamide crosslinking agent were uniformly added under mechanical stirring to prepare an aqueous gel electrolyte precursor solution. The cement powder and conductive filler are dry-mixed evenly, and the above-mentioned precursor solution is added and stirred evenly to prepare a main slurry without an initiation system for pumping and transportation. At the spray gun end of the spraying robot, the spare catalyst solution and initiator aqueous solution are simultaneously combined with the main slurry through independent liquid delivery channels, triggering an in-situ polymerization reaction at the moment of spraying, thus completing the spraying and forming of the modified cement-based composite slurry.
10. The construction method according to claim 8, characterized in that, Grinding controls surface roughness Ra≥30μm; during spraying, control spraying pressure 15 to 18MPa, spray gun speed 0.8 to 1.2m / s, and coating thickness error within ±0.5mm; Standard curing time is 20℃, relative humidity ≥95%, for 28 days; After evacuating to -0.09MPa and holding the pressure for 30 minutes, the test port is sealed.